Asymptotic stability for a thermoelectromagnetic material - Amendola, G. (Нелінійні коливання, 2001)
In this work we consider a linear thermoelectromagnetic material, whose behaviour is characterized by two rate-type equations for the heat flux and the electric current density. We derive the restrictions imposed by the laws of thermodynamics on the constitutive equations and introduce the free energy which yields the existence of a domain of dependence. Uniqueness, existence and asymptotic stability theorems are then proved.